Development and characterization of nettle-leaves powder (Urtica urens) as a potential supplement for animal feed - Arros, Francisca; Garrido, Camila; Valenzuela, Carolina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
Nettle plants in Chile are an underutilized resource. Its use in animal nutrition is also limited. In addition, information about its composition (specifically fatty acids and aminoacids) is scarce. The objective of this work was to develop and characterize nettle-leaves powder (NP). This powder was characterized by means of proximate chemical analysis. Its concentration of minerals, and composition profiles for fatty acids and aminoacids, was determined. NP showed high dry basis content of proteins (24%) and nitrogen-free extract (32%), whereas crude fiber concentration was low (8.4%). Also, NP showed high concentrations of ash (29%), and mineral, specially for calcium (1.65%) and zinc (20 mg/100g of NP). Additionally, glutamic and aspartic acids, as well as leucine, were the major types of aminoacids found in NP. In conclusion, though nettle plants are an under-utilized resource, the elevated content of protein found in powders prepared from their leaves might become a compelling reason to include them as a protein supplement in animal diets. Highlights Potential supplement for animal feed from nettle-leaves (Urtica urens). Re-use of a weed by a simple process of drying and grinding. The high content of proteins and minerals such as calcium and zinc. Amino acid profile with a high content of glutamic and aspartic acids, leucine and proline. Fatty acid profile with a predominance of polyunsaturated fatty acids, such as α linolenic and linoleic acids.